(3bWYI ef cJGH aj aVGFd GdUMGHIs
(3ChdgG (B:s
(3Chd GdehLhO hbJd GdVMGc HeQGM GgW ef GQV GdTGe SfI GQHY hSJjf ef GdaLQ hbjd (B: (3SfI SHY hSJjf hbHd (B: (3ZjQ Pdc s
(3BNQgG (B:s
(3hbGd GHh YHjOI SeYJ QShd Gddg Udi Gddg Ydjg hSde Hbhd NGdO Sja ef Sjha Gddg fYe aJj GdYTQI hefGbjI QVj Gddg Yfg Gd JMUj hcQGeGJg TgjQI dG JSJbUj aef Pdc s
(3UaMGJg GdKdGK cQQJ cd efgeG eQGJ aj GdJUhjQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3eJaQbGJs